Ta’lim Al-Lughah Al-Arabiyah li An-Nathiqin bi Ghairiha Raqmiyan - Mohammed Naji; Anas Malmus (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
This paper seeks to shed light on the extent to which technological applications contribute to improving and improving the process of teaching Arabic to non-native speakers, in addition to measuring the extent to which the field of teaching Arabic to non-native speakers is open to technological developments, by presenting and presenting some digital applications that can be invested in Arabic language classes. For non-native speakers, which aims to improve and renew the process of teaching Arabic to non-native speakers with distinction. Based on the foregoing, this paper stems from two main questions: 1) Has the field of teaching Arabic to non-native speakers opened up to technological development in a way that leads to its facilitation and modernization? 2) What role do digital applications and websites play in facilitating and improving the process of teaching Arabic to non-native speakers?تسعى هذه الورقة إلى تسليط الضوء على مدى إسهام التطبيقات التكنولوجية في تجويد وتحسين عملية تعليم اللغة العربية للناطقين بغيرها، علاوة على قياس مدى انفتاح مجال تعليم العربية للناطقين بغيرها على التطورات التكنولوجية، وذلك من خلال عرض وتقديم بعض التطبيقات الرقمية الممكن استثمارها في فصول تعليم اللغة العربية للناطقين بغيرها، والتي تهدف إلى تجويد وتجديد عملية تعليم اللغة العربية للناطقين بغيرها بامتياز.بناء على ما تقدم، فإن هذه الورقة تنطلق من سؤالين أساسيين هما: 1) هل انفتح مجال تعليم اللغة العربية للناطقين بغيرها على التطور التكنولوجي بالشكل الذي يؤدي إلى تيسيره وتحديثه؟ 2) وما الدور الذي تضطلع به التطبيقات والمواقع الرقمية في تيسير وتجويد عملية تعليم اللغة العربية للناطقين بغيرها؟